A hybrid axisymmetric conservative phase-field lattice Boltzmann method for hollow droplet migration - Qin, Ximei (Frontiers in Physics, 2023)
A hybrid axisymmetric conservative phase-field lattice Boltzmann method is applied to investigate the influence of Marangoni number (M a), density ratio (ρ r ) and radius ratio (R r ) on thermocapillary migration of deformable hollow droplet with variable fluid properties contrasts, where ρ r (R r ) is the density (radius) ratio of hollow part to the droplet. The isotherms show that heat transfer around hollow droplet is changed from conduction to convection with increase of M a. However, the temperature gradient across hollow droplet decreases with M a, which induces a small magnitude of migration velocity. When ρ r is increased, the isotherms are accumulated around hollow droplet front with large temperature gradient, which enhances the hollow droplet migration, while the migration velocity is decreased with the rise of R r . It is observed that thermocapillary migration of hollow droplet finally becomes a pure droplet with the influence of aforementioned parameters, and it experiences interface breaking and coalescing which causes a large transient variation of migration velocity. The magnitude of this transient variation of migration velocity is not obviously affected by M a, but significantly affected by ρ r and R r . The measured evolution of d (the dimensionless distance between inner and outer fronts of hollow droplet) demonstrates that ρ r has significant influence on the reduction rate of d in comparison with the influence of M a and R r . Similar influences on the relative migration velocity between fluid of hollow part inside droplet and sealed fluid of droplet are observed.